L’exil communiste espagnol en RDA : accueil, intégration, retour - Aurélie Denoyer (Cahiers de Civilisation Espagnole Contemporaine)
The exile of Spanish Communists in the GDR has remained largely unknown. As a consequence of Operation Bolero-Paprika, about a hundred Spaniards were received by the East German state. In this paper, we first propose to study the reception and integration of this group. Introducing a generational bias, we then examine the mechanisms that drove second-generation Spaniards to leave the GDR, a country in which they had grown up, to return in the 1970s to a Spain they did not know.